Investigation on the Interconnectivity in the Korean Financial Industry - 고현미; 김하영; 유재인 (금융안정연구, 2018)
Using weekly stock prices from 1990 to 2016, the trends and the connectivity of major institutions are estimated using Granger causality test and principal component analysis. According to the results, the statistical evidence of the strong connectivity during the financial crises in 1997 and 2008 was found. The connectivity index provides statistically significant information in predicting the changes in CD rates and long-short spreads over the two crises. According to sector-based analysis, commercial and merchant banks have played a significant role in heightening the systemic risks during the 1997 currency crisis, whereas commercial banks and the securities firms played a key role in the 2008 financial crisis.
Keywords: co-integration; Granger causality; interconnectivity; principal component analysis; systemic risk; 공적분; 그레인저 인과; 상호연계도; 주성분 분석; 시스템 리스크